A Chromosome—Level Genome Assembly of the Spotted Scat (Scatophagus argus) - Huang, Yuanqing (Genome Biol Evol, 2021)
The spotted scat, Scatophagus argus is a member of the family Scatophagidae found in Indo-Pacific coastal waters. It is an emerging commercial aquaculture species, particularly in East and Southeast Asia. In this study, the first chromosome-level genome of S. argus was constructed using PacBio and Hi-C sequencing technologies. The genome is 572.42 Mb, with a scaffold N50 of 24.67 Mb. Using Hi-C data, 563.28 Mb (98.67% of the genome) sequences were anchored and oriented in 24 chromosomes, ranging from 12.57 Mb to 30.38 Mb. The assembly is of high integrity, containing 94.26% conserved single-copy orthologues, based on BUSCO analysis. A total of 24,256 protein-coding genes were predicted in the genome, and 96.30% of the predicted genes were functionally annotated. Evolutionary analysis showed that S. argus diverged from the common ancestor of Japanese puffer (Takifugu rubripes) approximately 114.8 Ma. The chromosomes of S. argus showed significant correlation to T. rubripes chromosomes. A comparative genomic analysis identified 49 unique and 90 expanded gene families. These genomic resources provide a solid foundation for functional genomics studies to decipher the economic traits of this species.